Quality assessment of drinking water from roadside water dispensers in Miagao town proper. - Labios, Laize Sherie Laurente (2018.)
The study involved the quality assessment of the drinking water from roadside water dispensers in Miagao town proper, which was referred as A, B, C, K, L, and M. The drinking water from six roadside water dispensers were subjected to microbiological analysis and physico-chemical test. The microbiological analysis included the determination of Total Plate Count (TPC) and the Most Probable Number (MPN) of coliforms while the physico-chemical tests included the determination of pH and the temperature. The mean total plate counts for drinking water from roadside water dispensers A, B, C, K, L, and M were 8.93 x 102 CFU/mL, 2.51 x 103 CFU/mL, 2.51 x 103 CFU/mL, 8.61 x 102 CFU/mL, 1.47 x 103 CFU/mL, and 6.27 x 103 CFU/mL, and 6.27 x 103 CFU/mL, respectively, with source C having the lowest microbial count. For the MPN of coliforms, drinking water source A, B, C, K, L, and M, had 386 MPN/mL, 54 MPN/mL, 7 MPN/mL, 167 MPN/mL, 164 MPN/mL, and 190 MPN/mL, respectively. Total Plate Count and Most Probable Number of coliforms of all the drinking water source from roadside water dispensers were higher than the standard value set by the Philippine National Standard Drinking Water 2017. T-test of the location, the market site and away from the market site, showed a significance of 0.035, which means there was a significance in microbial quality as affected by the location. The pH of the drinking water from roadside water dispensers ranged from 6.72-7.03 pH of the drinking water were still within the ranged of the standard values set by the Philippine National Standards for Drinking Water 2017, which is 5.5-7 for drinking water undergone reverse osmosis or distillation, and 6.5-8.5 for general quality of water. The temperature of the drinking water from roadside water dispenser ranged from 15°C-25°C. The temperature has a strong positive correlation of 0.717 with the microbial load of the drinking water from water dispenser. It signifies that the temperature could affect the microbial load.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Water -- Microbiological analysis; Water -- Quality assessment